Introduction of paramedic led Echo in Life Support into the pre-hospital environment: The PUCA study. (March 2017) - Reed, Matthew J.; Gibson, Louise; Dewar, Alistair; Short, Steven; Black, Polly; Clegg, Gareth R.
Abstract: Objectives: Can pre-hospital paramedic responders perform satisfactory pre-hospital Echo in Life Support (ELS) during the 10-s pulse check window, and does pre-hospital ELS adversely affect the delivery of cardiac arrest care. Methods: Prospective observational study of a cohort of ELS trained paramedics using saved ultrasound clips and wearable camera videos. Results: Between 23rd June 2014 and 31st January 2016, seven Resuscitation Rapid Response Unit (3RU) paramedics attended 45 patients in Lothian suffering out-of-hospital CA where resuscitation was attempted and ELS was available and performed. 80% of first ELS attempts by paramedics produced an adequate view which was excellent/good or satisfactory in 68%. 44% of views were obtained within the 10-s pulse check window with a median time off the chest of 17 (IQR 13–20) seconds. A decision to perform ELS was communicated 67% of the time, and the 10-s pulse check was counted aloud in 60%. A manual pulse check was observed in around a quarter of patients and the rhythm on the monitor was checked 38% of the time. All decision changing scans involved a decision to stop resuscitation. Conclusions: Paramedics are able to obtain good ELS views in the pre-hospital environment but this may lead to longer hands off the chest time and possibly less pulse and monitor checking than is recommended. Future studies will need to demonstrate either improved outcomes or a benefit from identifying patients in whom further resuscitation and transportation is futile, before ELS is widely adopted in most pre-hospital systems.